Anwendung von Matrizen für algebraische Operationen mit trigonometrischen Reihen - Jasiulionis, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Ясюлёнис. Применение матриц при алгебраических действиях тригонометрических рядовA. Jasiulionis. Matricų taikymas trigonometrinių eilučių algebriniams veiksmams atlikti